2017
DOI: 10.1111/ijfs.13642
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioactive proteins and peptides from the diatom Nitzschia laevis and comparison of their in vitro antioxidant activities with those from Spirulina platensis and Chlorella vulgaris

Abstract: Summary This research focuses on green production of bioactive proteins and hydrolysates from Nitzschia. A comparison of antioxidant activities was established between protein extracts and hydrolysates from Nitzschia and two other well‐known microalgae, chlorella and spirulina. Protein hydrolysates from these microalgae were produced using Alcalase®, Flavourzyme® and Trypsin. The hydrolysis process enhanced the antioxidant activities in general, especially those obtained using Alcalase®. Nitzschia showed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Different studies suggest that TPC is a major contributor to the total antioxidant capacity (TAC) [41][42][43], whereas others contradict this claim [44,45]. Due to the highly oxidising nature of the Folin Ciocalteu reagent and the sample-colour interference, the results vary between studies [34,37,46,47]. In the present study, TPC showed a high correlation with the ORAC results (r = 0.90), suggesting that phenolic compounds did contribute significantly to spirulina's TAC.…”
Section: Effect Of Fermentation On Spirulinamentioning
confidence: 52%
See 1 more Smart Citation
“…Different studies suggest that TPC is a major contributor to the total antioxidant capacity (TAC) [41][42][43], whereas others contradict this claim [44,45]. Due to the highly oxidising nature of the Folin Ciocalteu reagent and the sample-colour interference, the results vary between studies [34,37,46,47]. In the present study, TPC showed a high correlation with the ORAC results (r = 0.90), suggesting that phenolic compounds did contribute significantly to spirulina's TAC.…”
Section: Effect Of Fermentation On Spirulinamentioning
confidence: 52%
“…According to Boussiba and Richmond [5], C-PC has a molecular weight of 44 kDa. However, lower molecular weight trimers of this peptide-bond pigment have been identified in previous research, to be between 14.4 and 30 kDa [47], which explains the appearance of a broad band at~16-17 kDa, just below the 18.4 kDa marker. These have been identified in previous studies as alpha and beta subunits of C-PC, with molecular masses of 16 and 17 kDa [51,62].…”
Section: Effect Of Fermentation On Spirulinamentioning
confidence: 71%
“…These include hydrolyzates and peptides from the red alga Palmaria palmata (Harnedy et al, ), processed fish wash water (Zhou et al, ), chicken blood cells (Zheng, Si, Ahmad, Li, & Zhang, ), squid pen chitosan (Shavandi et al, ), abalone viscera (Je, Park, Hwang, & Ahn, ), pearl oysters (Ma, Wu, & Li, ), rice bran (Phongthai et al, ), mulberry leaf (Sun et al, ), and silkworm (Liu, Wan, Liu, Zou, & Liao, ). Others include microorganisms and single cell organisms (Alzahrani, Perera, & Hemar, ), blood clam (Chi, Hu, Wang, Li, & Ding, ), and echinoderm byproducts (Mamelona, Saint‐Louis, & Pelletier, ). As summarized in Table , the enzymes used for the production of antioxidative hydrolyzates and peptides from food proteins are as diverse as the sources themselves and range from food grade proteases such as Alcalase, Flavourzyme, Neutrase, and Protamex to the pepsin/pancreatin enzyme system used for simulated GIT digestion.…”
Section: Production Of Antioxidant Enzymatic Protein Hydrolyzatesmentioning
confidence: 99%
“…Moreover, DPPH scavenging activities from our Nitzschia sp. (34.04%) were in accordance with those from Nitzschia laevis protein hydrolysates obtained using Trypsin, Alcalase or Flavourzyme (Alzahrani et al ., ). However, higher DPPH scavenging activity (around 70%) was obtained from Spirulina platensis crude hydrolysates in the works of Yu et al .…”
Section: Resultsmentioning
confidence: 97%